2008
DOI: 10.1590/s0102-86502008000700024
|View full text |Cite
|
Sign up to set email alerts
|

Morphological aspects of mural thrombi deposition residual lumen route in infrarenal abdominal aorta aneurisms

Abstract: Purpose: To assess the most frequent deposition site of mural thrombi in infrarenal abdominal aorta aneurisms, as well as the route of the residual lumen. Methods: Assessment of CT scan images from 100 patients presenting asymptomatic abdominal aorta aneurism, and followed at HC-FMRP-USP. Results: In 53% of the cases the mural thrombus was deposited on the anterior wall; from these, in 22%, the residual lumen described a predominantly right sided route; in 22%, a left sided route; on the mid line in 5%; and cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Platelets then preferentially attach to pre-existing ILT or to the distal regions of the vessel (AAA). This is supported by multiple anatomic studies of ILT, as it commonly occurs in the distal anterior region of AAA [23,[41][42][43]. In 2012, an integrated fluid-chemical approach for modelling ILT formation in AAA was introduced by Biasetti et al which showed agreement with the site specificity of ILT formation and the movement of vortex structures [44].…”
Section: Introductionmentioning
confidence: 91%
“…Platelets then preferentially attach to pre-existing ILT or to the distal regions of the vessel (AAA). This is supported by multiple anatomic studies of ILT, as it commonly occurs in the distal anterior region of AAA [23,[41][42][43]. In 2012, an integrated fluid-chemical approach for modelling ILT formation in AAA was introduced by Biasetti et al which showed agreement with the site specificity of ILT formation and the movement of vortex structures [44].…”
Section: Introductionmentioning
confidence: 91%
“…Moreover, there were differences in measured parameter concentrations between thin and thick ILT sections. wall adjacent to thin ILT vs. thin ILT (p = 0.03), 3 wall adjacent to thin ILT vs. thick ILT (p = 0.0004), 4 wall adjacent to thick ILT vs. thick ILT (p = 0.00002), 5 wall adjacent to thick ILT vs. thin ILT (p = 0.004), 6 wall adjacent to thin ILT vs. thin ILT (p = 0.01), 7 wall adjacent to thin ILT vs. thick ILT (p = 0.006), 8 wall adjacent to thin ILT vs. wall adjacent to thick ILT (p = 0.002), 9 wall adjacent to thin ILT vs. thin ILT (p = 0.006), 10 wall adjacent to thin ILT vs. thick ILT (p = 0.002), 11 wall adjacent to thick ILT vs. thick ILT (p = 0.0003), 12 wall adjacent to thick ILT vs. thin ILT (p = 0.0006), 13 wall adjacent to thin ILT vs. thin ILT (p = 0.0004), 14 wall adjacent to thin ILT vs. thick ILT (p = 0.0002), 15 wall adjacent to thick ILT vs. thick ILT (p = 0.003), 16 wall adjacent to thick ILT vs. thin ILT (p = 0.009), 17 wall adjacent to thin ILT vs. thin ILT (p = 0.02), 18 wall adjacent to thin ILT vs. thick ILT (p = 0.02), 19 wall adjacent to thin ILT vs. wall adjacent to thick ILT (p = 0.00005), 20 wall adjacent to thick ILT vs. thick ILT (p = 0.00005), 21 wall adjacent to thick ILT vs. thin ILT (p = 0.00004). 2 wall adjacent to thin ILT vs. thin ILT (p = 0.03), 3 wall adjacent to thin ILT vs. thick ILT (p = 0.0004), 4 wall adjacent to thick ILT vs. thick ILT (p = 0.00002), 5 wall adjacent to thick ILT vs. thin ILT (p = 0.004), 6 wall adjacent to thin ILT vs. thin ILT (p = 0.01), 7 wall adjacent to thin ILT vs. thick ILT (p = 0.006), 8 wall adjacent to thin ILT vs. wall adjacent to thick ILT (p = 0.002), 9 wall adjacent to thin ILT vs. thin ILT (p = 0.006), 10 wall adjacent to thin ILT vs. thick ILT (p = 0.002), 11 wall adjacent to thick ILT vs. thick ILT (p = 0.0003), 12 wall adjacent to thick ILT vs. thin ILT (p = 0.0006), …”
Section: Neutrophil Mediator Distribution In Abdominal Aortic Aneurysmmentioning
confidence: 99%
“…An AAA is usually asymmetric, and an ILT is often circumferential with the thickest part on the AAA’s ventral side [ 11 , 12 , 13 , 14 ]. The thickness of a thrombus and/or the aortic wall may differ between different patients or along each aneurysm [ 5 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their postulate is somewhat confirmed by multiple anatomic studies showing eccentric volume distributions of ILT with some prevalence seen in the distal anterior region of the AAA. 7,11,12,23 Based on a computational analysis, Rayz et al . 27 observed thrombus deposition in certain regions of three patient-specific geometries with an increase in “flow residence time” and low AAA wall shear stress.…”
Section: Introductionmentioning
confidence: 99%